Neural correlates of emotion regulation deficits in remitted depression: the influence of regulation strategy, habitual regulation use, and emotional valence - Kanske, Philipp; Schönfelder, Sandra; Wessa, Michèle (NeuroImage, 2012)
Regulating emotions through reappraisal has been shown to elicit abnormal neural activation patterns in currently depressed patients. It is, however, unclear if this deficit generalizes to other emotion regulation strategies, if it persists when patients recover, and if it is related to habitual use of reappraisal strategies. Therefore, we measured the neural responses to emotional images with functional magnetic resonance imaging in remitted patients with previous episodes of major depression and healthy controls. While viewing the images participants regulated the elicited emotions using either a reappraisal or a distraction strategy. Habitual reappraisal use was measured with the Cognitive Emotion Regulation Questionnaire. Depressed patients showed a selective deficit in down-regulating amygdala responses to negative emotional stimuli using reappraisal. This down-regulation of amygdala activity was strongest in participants high in habitual reappraisal use. Activity in the regulating control-network including anterior cingulate and lateral orbitofrontal cortex was increased during both emotion regulation strategies. The findings in remitted patients with previous episodes of major depression suggest that altered emotion regulation is a trait-marker for depression. This interpretation is supported by the relation of habitual reappraisal use to amygdala down-regulation success.